2018
DOI: 10.2174/1871520617666170912124258
|View full text |Cite
|
Sign up to set email alerts
|

α-Aroylketene Dithioacetal Mediated Synthesis of (E)-3-(benzo[d]thiazol-2-ylamino)-2-(1-methyl-1H-indole-3-carbonyl)-3-(methylthio)acrylonitrile Derivatives and their Biological Evaluation

Abstract: Among the compounds synthesized some of the compounds possess significant anticancer, antioxidant and anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Acrylonitrile compounds are easily linked to aromatic rings, heterocycles and other structures, resulting in many new compounds. Acrylonitrile compounds are an effective antimalarial drug with good antioxidant and anti‐inflammatory properties 1 . Studies have shown that some derivatives have anti‐proliferative effects on U937, K562, Jurkat, and HeLa Tumor cells and are effective inducers of tumor cell apoptosis 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Acrylonitrile compounds are easily linked to aromatic rings, heterocycles and other structures, resulting in many new compounds. Acrylonitrile compounds are an effective antimalarial drug with good antioxidant and anti‐inflammatory properties 1 . Studies have shown that some derivatives have anti‐proliferative effects on U937, K562, Jurkat, and HeLa Tumor cells and are effective inducers of tumor cell apoptosis 2,3 .…”
Section: Introductionmentioning
confidence: 99%